Maternal and neonatal outcomes associated with different anesthetic techniques in cesarean delivery for multiple gestations: A retrospective study of 1,057 patients - Patchareya Nivatpumin (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: The aim of the present study was to examine maternal and neonatal outcomes of cesarean delivery for multiple gestations using different anesthetic techniques. Materials and Methods: A retrospective chart review of 1,057 pregnant women with multiple gestations undergoing cesarean delivery in 10-year period (August 2006 to December 2015) was performed. Patient demographic characteristics, choices of anesthesia, intra-operative data and complications were collected. Maternal and neonatal complications were compared between spinal anesthesia [SA] and general anesthesia [GA]. Results: A total of 984 (93.1%) patients received SA, whereas 73 (6.9%) received GA. The incidence of intra-operative maternal hypotension and the proportion of patients requiring vasopressors were higher in the SA than GA group (p<0.001). The intra-operative estimated blood loss volume was significantly higher in the GA than SA group (p = 0.007). Among peripartum complications, the rate of postpartum hemorrhage (p = 0.003), the rate of blood transfusion (p = 0.001), and the rate of hysterectomy (p<0.001) were significantly higher in the GA than SA group. However, there was no difference in the incidence of uterine atony between the two groups. The neonatal Apgar scores at 1 and 5 minutes of first- and second-born neonates were significantly higher in the SA than GA group (p<0.001). Although the neonatal death rate was not significantly different between the groups, the rate of birth asphyxia was significantly higher in first- and second-born neonates from women in the GA group (p<0.001). Conclusion: General anesthesia in women with multiple gestations undergoing cesarean delivery is associated with more complications than SA. Since this is a retrospective study, whether SA is a preferable anesthetic of choice in these patients needs further study.